Geochemical characterization of Neogene sediments from onshore West Baram Delta Province, Sarawak: Paleoenvironment, source input and thermal maturity - Togunwa, O.S. (De Gruyter Open Ltd, 2017)
The Neogene strata of the onshore West Baram Province of NW Borneo contain organic rich rock formations particularly within the Sarawak basin. This basin is a proven prolific oil and gas province, thus has been a subject of great interest to characterise the nature of the organic source input and depositional environment conditions as well as thermal maturation. This study is performed on outcrop samples of Lambir, Miri and Tukau formations, which are of stratigraphic equivalence to the petroleum bearing cycles of the offshore West Baram delta province in Sarawak. The investigated mudstone samples are organic rich with a total organic carbon (TOC) content of more than 1.0 wt.. The integration of elemental and molecular analyses indicates that there is no significant variation in the source input between these formations. The investigated biomarkers parameters achieved from acyclic isoprenoids, terpanes and steranes biomarkers of a saturated hydrocarbon biomarkers revealed that these sediments contain high contribution of land plants with minor marine organic matter input that was deposited and preserved under relatively oxic to suboxic conditions. This is further supported by low total sulphur (TS), high TOC/TN ratios, source and redox sensitive trace elements (V, Ni, Cr, Co and Mo) concentrations and their ratios, which suggest terrigenous source input deposited under oxic to suboxic conditions. Based on the analysed biomarker thermal maturity indicators, it may be deduced that the studied sediments are yet to enter the maturity stage for hydrocarbon generation, which is also supported by measured vitrinite reflectance values of 0.39-0.48 Ro. © 2017 O. S. Togunwa and W. H. Abdullah.